LONG TERM TRENDS IN THE GROWTH AND STRUCTURE OF THE NET STATE DOMESTIC PRODUCT IN KERALA - Mohanan Pillai, P and Shanta, N (Centre for Development Studies-WP376, 2005)
Kerala has been a model to other states for her achievements in social development. But in terms of economic growth her performance has for long been very poor and a matter of deep concern. In this context the turnaround in growth that has occurred in Kerala in the nineties , in contrast to the earlier decades needs to be looked at in detail. This study is an attempt in that direction. It is an analysis of the long terms trends in the State Domestic Product of Kerala for the period 1970-2000. It is concerned with the growth of the different sectors of the economy, the changes in the sectoral composition of output and other related issues such as the sources of growth. What is observed is that in the eighties and more so in the nineties both in terms of rates of growth and share in net state domestic product the tertiary sector has dominated and this has been due to the growth of the producer's services. Income responsiveness of producer services is also found to be the highest. However, it is observed that this has not resulted in any linkages with the production sector within the economy suggesting that the linkages may be with productive sectors of other states. Nevertheless there are some intersectoral linkages with the consumer services and intra sectorallinkages between banking and insurance and transport by other means. In conclusion the leading and lagging sectors of the economy and in the nineties the sectors propelling growth are identified. The sectors which have lost their position when compared to the previous decades are Registered Manufacturing, Construction and Public Administration. The emerging sectors in the economy are transport by other means, and trade , hotels and restaurants while banking and insurance is the leading sector. Analysis of structural transformation in the economy suggests that although structural change has been there, it was found to be very moderate and has not been strong enough to bring about a major change either in terms of the growth centres of the economy or the main contributors to the growth of the economy. In conclusion one feels that we continue to remain a consumer /trading state and not a producer state. Is this socially desirable and sustainable is a question that needs to be addressed.